Advancing the Management of Anaplastic Thyroid Carcinoma: A Case Study of Multimodal Therapy and the Role of Emerging Nuclear Medicine Infrastructure in Bangladesh (Bangladesh Journal of Nuclear Medicine, 2025)
Anaplastic thyroid carcinoma (ATC) is an aggressive and rare form of thyroid cancer, representing 1-2% of thyroid malignancies but accounting for the majority of thyroid cancer-related deaths due to its rapid progression, invasiveness, and resistance to standard therapies. This report highlights the case of a 60-year-old male histopathologically diagnosed with ATC stage IV as there were lymph node metastases. The patient was managed with a multidisciplinary team approach and had total thyroidectomy followed by systemic chemotherapy and three-dimensional conformal radiotherapy. The reported case highlights the importance of aggressive, integrated therapeutic approaches in managing ATC, emphasizing personalized, multidisciplinary care, advanced radiotherapy techniques, and molecular-targeted therapies for improved outcomes.Bangladesh J. Nuclear Med. 28(1): 164-169, 2025